2014
DOI: 10.2217/bmm.14.1
|View full text |Cite
|
Sign up to set email alerts
|

Brain Autoantibodies in Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder characterized by impairments in reciprocal social interactions as well as restricted, repetitive and stereotyped patterns of behavior. The etiology of ASD is not well understood, although many factors have been associated with its pathogenesis, such genetic, neurological, environmental and immunological factors. Several studies have reported the production of numerous autoantibodies that react with specific brain proteins and brain tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 65 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…Autoimmunity in autism is more organ-specific (i.e., brain) and not multisystemic such as systemic lupus erythematosus. Majority of studies reported high prevalence of brain-specific auto-antibodies in children with autism [8,19]. A recent study has reported low prevalence of anti-dsDNA and antinuclear antibodies (34 and 25%, respectively) in children with autism [26].…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmunity in autism is more organ-specific (i.e., brain) and not multisystemic such as systemic lupus erythematosus. Majority of studies reported high prevalence of brain-specific auto-antibodies in children with autism [8,19]. A recent study has reported low prevalence of anti-dsDNA and antinuclear antibodies (34 and 25%, respectively) in children with autism [26].…”
Section: Discussionmentioning
confidence: 99%
“…ASD is of unknown etiology. Genetic components such as mutations [121] , epigenetic disorders such as altered methylaton [122] , abnormal cytokine profile where inflammatory signals dominate [15] , and environmental factors such as pollutants [123] or immune responses to infections [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] appear to contribute to ASD. However, whichever it may be the invoked causal factor, the mechanism(s) at the basis of ASD remain unsettled.…”
Section: Discussionmentioning
confidence: 99%
“…There is a clinical and epidemiological consensus that infections may be causally involved in the neurodevelopmental and behavioural disturbances that characterize ASD [1][2][3][4][5][6] . Specifically, a main role in the pathophysiology of ASD has been repeatedly suggested for the activation of the immune system against the infectious agents [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] rather than to viral/microbial activities per se, such as, for example, subversion of the host protein synthesis machinery [22] , manipulation of membrane transport pathways [23] , and up-regulation of HLA-E expression with, consequently, suppression of NK cell recognition [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…Autism Spectrum Disorder (ASD) is a group of neurodevelopmental disorders defined by an abnormal functioning with the fundamental deficits in social communication and reciprocity, and shows repetitive and categorized patterns of behavior [1,2]. ASD is one of the most common behavioral disabilities diagnosed in children, which represent a major public health problem.…”
Section: Introductionmentioning
confidence: 99%